Progress in dense magnetized plasma research in Poland; a review - Sadowski, M.J. (Вопросы атомной науки и техники, 2000)
This invited talk describes recent dense magnetized plasma (DMP) experiments carried out with different Plasma-Focus (PF) facilities in Poland, which were investigated at energy levels ranging from 40 kJ to about 800 kJ. The most important results, which were obtained with MAJA-PF and PF-360 devices in Swierk, are presented. Also presented are some results obtained with PF-150 and PF-1000 facilities at IFPiLM in Warsaw. The main trends of the present DMP research are described and commented.